Ecosystem service of green infrastructure for adaptation to urban growth: function and configuration - Yun-Cai Wang (Taylor & Francis Group, 2018)
Objectives: (1) to explore what kind of green infrastructure (GI) meets the demand for urban ecological security of rapid urbanization areas; (2) to figure out how to determine the specific function and configuration of GI from ecosystem service requirements of urban ecological security. Methods: (1) Through the literature review, this article summarizes the function and structure evolution of GI in order to adapt to urban growth. (2) Standing on the imperfect ecological functions and unreasonable spatial configurations, this article builds up a conceptual model for the optimization of green infrastructure ecosystem services to meet the demand for the green infrastructure pattern needed by urban growth. Results: The optimization framework consists of four central function modules and its regulating and controlling mechanisms, including: (1) Balancing supply and demand of GI’s ecosystem service; (2) Measuring and evaluating GI’s ecosystem services; (3) Elevating and optimizing GI’s ecosystem service; (4) Building urban ecological security pattern with high efficiency of GI’s ecosystem services. Moreover, this framework provides guidance for the planning and design of GI and the urban ecological security pattern building in rapid urbanization areas based on balancing supply and demand of GI’s ecosystem services. Conclusion: The conceptual model of GI’s ecosystem service optimization based on balancing supply and demand shows a new path to meet the needs of urban growth and build a city's ecological security pattern through upgrading and optimizing GI.